2020
DOI: 10.1007/s40123-020-00247-9
|View full text |Cite
|
Sign up to set email alerts
|

Vision Loss from Atypical Optic Neuritis: Patient and Physician Perspectives

Abstract: This article, co-authored by a patient affected by bilateral, recurrent, atypical optic neuritis, and clinicians, discusses the mental burden of living with uncertainty and the possibility of further sight loss, along with the side effects of treatment. The patient shares some of the challenges, coping strategies, and the value they found in creating and participating in a patient support group. The physicians consider whether current clinical measures adequately capture the outcomes that matter to patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…These groups are useful to share experiences and discuss helpful practices to manage conditions. 34 For patients undergoing surgery, online support groups can also help elucidate details of the peri-operative expectations, increase motivation, and help patients and caregivers feel understood. 35 Undoubtedly, multilingual patient education materials and support groups contribute heavily towards patient competence and health outcomes.…”
Section: Regionmentioning
confidence: 99%
“…These groups are useful to share experiences and discuss helpful practices to manage conditions. 34 For patients undergoing surgery, online support groups can also help elucidate details of the peri-operative expectations, increase motivation, and help patients and caregivers feel understood. 35 Undoubtedly, multilingual patient education materials and support groups contribute heavily towards patient competence and health outcomes.…”
Section: Regionmentioning
confidence: 99%
“…The possibility to display images directly to the individuals and discuss changes has given them more confidence and insight in their care. 35 This good partnership has helped in working together to build trust, supporting treatment decisions and making OCT scans available for research. There is a need to maintain this mutual trust at a time where the immense amount of data accumulated now permit AI‐inspired projects on big data.…”
Section: The Patient Voicementioning
confidence: 99%
“…It is noninvasive, noncontact, quick, and provides instant feedback. The possibility to display images directly to the individuals and discuss changes has given them more confidence and insight in their care 35 . This good partnership has helped in working together to build trust, supporting treatment decisions and making OCT scans available for research.…”
Section: The Patient Voicementioning
confidence: 99%
“…For example, visual impairment has been independently associated with several mental health conditions, including depression [4][5][6][7], anxiety [5,6,8], and posttraumatic stress disorder [9]. Several studies report that eye care patients experience degrees of emotional trauma and may require some form of mental health support [10,11] which should not be limited to patients with recent diagnoses of an eye condition [10,12,13]. In addition, it has been shown that anxiety is one of the main reasons for clinic non-attendance at eye clinics [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%